Composition
By using the adhesive layer formed by multiple bonding parts in an all-solid-state battery, the contact point distribution between the electrode layer and the current collector is optimized, and the problem of increasing internal resistance of the battery is solved, thereby achieving lower internal resistance and higher battery performance.
Patent Information
- Application Number
- JP2021192818
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Filing Date
- 2021-11-29
- Publication Date
- 2025-04-08
- Estimated Expiration
- 2041-11-29
AI Technical Summary
The electrode integrated structure of existing all-solid state batteries causes an increase in the gap between the current collector and the electrode layer, resulting in an increase in the internal resistance of the battery.
The adhesive layer formed in the stripe or dot-like mode is used to ensure the distribution of contact points between the electrode layer and the current collector, satisfying the specific gap ratio and curvature width conditions of the electrode layer to reduce the internal resistance of the battery.
By optimizing the contact point distribution between the electrode layer and the current collector, the internal resistance of the all-solid state battery is significantly reduced, and the performance and durability of the battery are improved.
Smart Images

Figure 0007658257000002 
Figure 0007658257000003 
Figure 0007658257000004
Abstract
Description
[Technical field]
[0001] The present disclosure relates to compositions. [Background technology]
[0002] All-solid-state batteries have attracted attention because they use a solid electrolyte instead of an electrolytic solution containing an organic solvent as the electrolyte between the positive and negative electrodes.
[0003] Patent Document 1 discloses an all-solid-state battery having an adhesive means for adhering a current collector to a battery unit stacked adjacent to the current collector. [Prior art documents] [Patent documents]
[0004] [Patent Document 1] JP 2017-204377 A Summary of the Invention [Problem to be solved by the invention]
[0005] There is a demand for reducing the resistance of all-solid-state batteries. In Patent Document 1, a hot melt adhesive is used as an adhesive, and the hot melt adhesive is arranged in an L-shape at the corners of the battery unit. The area in which the hot melt adhesive is arranged in the battery unit is small, and when the current collector and the electrode layer are integrated, a gap is created between the current collector and the electrode layer due to the undulation of the electrode layer, which increases the resistance. In addition, in the area where there is no adhesive, a gap is created between the electrode layer and the current collector, which increases the resistance.
[0006] The present disclosure has been made in consideration of the above-mentioned circumstances, and has a main object to provide a composition that can reduce the resistance of an all-solid-state battery. [Means for solving the problem]
[0007] The composition of the present disclosure is a composition for an all-solid-state battery having a first electrode layer, a current collector, and a second electrode layer in this order, a part of a contact surface of each of the first electrode layer and the second electrode layer with a current collector is bonded to the current collector by an adhesive layer; the adhesive layer is composed of a plurality of adhesive portions arranged in a stripe pattern or a dot pattern on a contact surface between the current collector and the electrode layer, where x is the distance between adjacent adhesive portions on the same surface, and y is the shortest distance in a surface direction between the adhesive portion on the front surface side and the adhesive portion on the back surface side of the current collector when viewed in a plane, 2y / x≧0.75 is satisfied, The electrode layer has a curved width R that satisfies R≧2x. Effect of the Invention
[0008] The present disclosure can provide a composition that can reduce the resistance of an all-solid-state battery. [Brief description of the drawings]
[0009] [Figure 1] FIG. 1 is a schematic diagram showing an example of a current collector in which adhesive portions are applied in a dot pattern on the front and back surfaces of the current collector. [Diagram 2] FIG. 2 is a schematic cross-sectional view showing an example of a current collector having adhesive portions disposed on the front and back sides. [Diagram 3] FIG. 3 is a diagram showing an example of a current collector foil for explaining a coating boundary. [Figure 4] FIG. 4 is a diagram showing an example of a laminate including an electrode layer for explaining a method for measuring the curvature width. [Diagram 5] FIG. 5 is a schematic cross-sectional view showing an example of a current collector and an electrode layer. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0010] The composition of the present disclosure is a composition for an all-solid-state battery having a first electrode layer, a current collector, and a second electrode layer in this order, a part of a contact surface of each of the first electrode layer and the second electrode layer with a current collector is bonded to the current collector by an adhesive layer; the adhesive layer is composed of a plurality of adhesive portions arranged in a stripe pattern or a dot pattern on a contact surface between the current collector and the electrode layer, where x is the distance between adjacent adhesive portions on the same surface, and y is the shortest distance in a surface direction between the adhesive portion on the front surface side and the adhesive portion on the back surface side of the current collector when viewed in a plane, 2y / x≧0.75 is satisfied, The electrode layer has a curved width R that satisfies R≧2x.
[0011] [Components] The composition of the present disclosure has a first electrode layer, a current collector, and a second electrode layer in this order, with a portion of the contact surface of each electrode layer with the current collector being adhered to the current collector by an adhesive layer.
[0012] [Adhesive layer] The adhesive layer is composed of a plurality of adhesive portions arranged in a stripe or dot pattern on the contact surface between the current collector and the electrode layer. Therefore, only a part of the contact surface of each electrode layer with the current collector is bonded to the current collector by the adhesive layer, and the entire contact surface does not have to be bonded. The striped pattern means a striped pattern. The striped pattern may be either vertical or horizontal, as long as the stripes are parallel. The dot pattern means a polka dot pattern.
[0013] FIG. 1 is a schematic diagram showing an example of a current collector in which adhesive portions are applied in a dot pattern on the front and back surfaces of the current collector. 1, adhesive portions 1 are arranged in a dot pattern on the front and back surfaces of a current collector 2. The W direction indicates the width direction of the current collector 1, and the H direction indicates the depth direction of the current collector.
[0014] The adhesive portion may be a glue line or a glue dot. The size of the adhesive dots that become dots is not particularly limited, and when the adhesive dots are regarded as circles, the diameter may be 0.1 mm to 1 mm. The number of adhesive lines on the same surface may be three or more, and there is no particular upper limit. The length of the adhesive line may be, for example, 1 to 10 mm. The distance x (pitch x) (mm) between adjacent adhesive portions on the same surface may be 2 mm or more and 4 mm or less. When the component is viewed in plan, the shortest distance in the planar direction between the adhesive part on the front side of the current collector and the adhesive part on the back side of the current collector is y, which may be 1 mm or more and 2 mm or less, where y is the offset distance of the adhesive part on the back side of the current collector relative to the adhesive part on the front side of the current collector. The composition of the present disclosure only needs to satisfy condition (1) of 2y / x≧0.75, which means that the adhesive portions on the front and back surfaces of the current collector are arranged so as to be offset from each other.
[0015] FIG. 2 is a schematic cross-sectional view showing an example of a current collector having adhesive portions disposed on the front and back sides. As shown in Fig. 2, adhesive portions 1 are arranged on the front and back sides of a current collector 2. x is the distance (pitch) between adjacent adhesive portions on the same surface, y is the shortest distance in the planar direction between adhesive portion 1 on the front side and adhesive portion 1 on the back side of the current collector, and z is a non-shortest distance in the planar direction between adhesive portion 1 on the front side and adhesive portion 1 on the back side of the current collector.
[0016] The adhesive used in the adhesive layer is not particularly limited as long as it is solid and has an adhesive function. Examples of the adhesive include a tacky resin and a hot melt agent. Examples of the tacky resin include an acrylic resin, a rubber resin, a silicone resin, and a urethane resin. The hot melt agent is not particularly limited as long as it is a resin with a melting point of 140° C. or less, and examples of the hot melt agent include an ethylene-vinyl acetate resin.
[0017] [Electrode layer] The configuration of the present disclosure only needs to satisfy condition (2) that the curvature width R of each electrode layer satisfies R≧2x. The positions of the adhesive parts on the front and back surfaces of the current collector are shifted so as to satisfy 2y / x≧0.75, and the electrode layer and the current collector are bonded by the adhesive layer at a pitch x smaller than the waviness (curvature width R) of the electrode layer. This makes it possible to correct the waviness of the electrode layer with the adhesive layer. In addition, by shifting the positions of the adhesive parts on the front and back surfaces, the reaction force of the electrode layer can be dispersed, making it possible to reduce the resistance of the all-solid-state battery after endurance testing.
[0018] FIG. 3 is a diagram showing an example of a current collector foil for explaining a coating boundary. In this disclosure, when adhesive is applied to a current collector (current collecting foil) by spot application as shown in FIG. 3, in a system in which the adhesive is applied periodically, the distance from any edge of the current collecting foil on the front surface in a planar view to the closest center of the adhesive portion is defined as plane coordinate (W1, H1), and the distance from any corner of the front surface on the back surface in a planar view to the closest center of the adhesive is defined as plane coordinate (W2, H2), and the boundary between the current collector and the adhesive is perpendicular to the line connecting the plane coordinate (W1, H1) and the plane coordinate (W2, H2) in a planar view.
[0019] FIG. 4 is a diagram showing an example of a laminate including an electrode layer for explaining a method for measuring the curvature width. The laminate shown in Fig. 4 has a negative electrode current collector foil, a negative electrode layer, a solid electrolyte layer (SE layer), and a positive electrode layer in this order, and the sides are fixed with tape. The size of the positive electrode layer shown in Fig. 4 is 70.0 mm x 70.0 mm, the same as in Example 1 described later. The curvature width (waviness width) R may be measured, for example, by the following method. In a plan view, the height (thickness) of the positive electrode layer on a line that divides the positive electrode layer, which is the electrode layer to be measured, into four equal parts in a direction perpendicular to the direction of the coating boundary is measured with a laser film thickness gauge at a pitch of approximately 5.5 μm in the surface direction, and the slope every 100 μm is calculated.The distance between adjacent points where the slope changes from positive to negative or the distance between adjacent points where the slope changes from negative to positive is calculated, and the minimum value thereof can be measured as the curvature width (waviness width) R. The curvature width R may be calculated by measuring the height of the electrode layer in a direction perpendicular to the application boundary of the adhesive portion and calculating it as the minimum value of the distance between adjacent peaks or the minimum distance between adjacent valleys.
[0020] FIG. 5 is a schematic cross-sectional view showing an example of a current collector and an electrode layer. As shown in Figure 5, for example, the curvature width R of the electrode layer may be the minimum value of the distance in the plane direction from one peak of the electrode layer to the next peak where the distance in the height direction from the electrode layer to the current collector is maximum, based on the contact surface between the current collector 2 and the electrode layer 3.
[0021] The electrode layer contains an electrode active material, and optionally contains a solid electrolyte, a conductive material, a binder, and the like. The electrode layer is a positive electrode layer or a negative electrode layer. Two electrode layers having different types of electrode active materials may be prepared, and one may be used as a positive electrode layer and the other as a negative electrode layer. One of the first electrode layer and the second electrode layer may be a positive electrode layer and the other a negative electrode layer, or both may be positive electrode layers, or both may be negative electrode layers. As the electrode active material, any material that can be used as an active material for an all-solid-state battery can be used, and materials similar to those exemplified as the positive electrode active material and the negative electrode active material described later can be used. As the solid electrolyte, the same ones as those exemplified in the solid electrolyte layer described later can be exemplified. Examples of the conductive material and binder include the same materials as those exemplified for the positive electrode layer described below. The thickness of the electrode layer is not particularly limited, but may be, for example, 10 to 100 μm, or 10 to 20 μm.
[0022] [Current collector] As the current collector, the same ones as those exemplified as the positive electrode current collector and the negative electrode current collector described later can be used.
[0023] [All-solid battery] The composition of the present disclosure is a composition for an all-solid-state battery. The all-solid-state battery of the present disclosure may have an electrode laminate including a positive electrode including a positive electrode layer and a positive electrode current collector, a solid electrolyte layer, and a negative electrode including a negative electrode layer and a negative electrode current collector. The all-solid-state battery of the present disclosure may be an all-solid-state battery stack in which a plurality of electrode laminates are stacked. The all-solid-state battery may have at least one laminate unit including a positive electrode, a solid electrolyte layer, a negative electrode, a negative electrode, a solid electrolyte layer, and a positive electrode in this order. The all-solid-state battery may have at least one laminate unit including a positive electrode, a solid electrolyte layer, a negative electrode, a positive electrode, a solid electrolyte layer, and a negative electrode in this order. The all-solid-state battery may have, in this order, the components of the present disclosure: a first electrode layer, a current collector, and a second electrode layer. One of the first electrode layer and the second electrode layer may be a positive electrode layer and the other may be a negative electrode layer, or both may be positive electrode layers, or both may be negative electrode layers. The current collector may be a positive electrode current collector, a negative electrode current collector, or a combination of these.
[0024] [Positive electrode] The positive electrode includes a positive electrode layer and a positive electrode current collector.
[0025] [Positive electrode layer] The positive electrode layer contains a positive electrode active material, and may contain optional components such as a solid electrolyte, a conductive material, and a binder.
[0026] There is no particular limitation on the type of positive electrode active material, and any material that can be used as an active material for an all-solid-state battery can be used. Examples of the positive electrode active material include metallic lithium (Li), lithium alloys, and LiCoO 2 , LiNi 0.8 Co 0.15 Al 0.05 O 2 , LiNi x Co 1-x O 2 (0 <x<1)、LiNi 1 / 3 Co 1 / 3 Mn 1 / 3 O 2 , LiMnO 2, Li-Mn spinel substituted with different elements, lithium titanate, lithium metal phosphate, LiCoN, Li 2 SiO 3 , and Li 4 SiO 4 , transition metal oxide, TiS 2 , Si, SiO 2 , Si alloys, and lithium-storing intermetallic compounds. The Li-Mn spinel substituted with a different element is, for example, LiMn 1.5 Ni 0.5 O 4 , LiMn 1.5 Al 0.5 O 4 , LiMn 1.5 Mg 0.5 O 4 , LiMn 1.5 Co 0.5 O 4 , LiMn 1.5 Fe 0.5 O 4 , and LiMn 1.5 Zinc 0.5 O 4 Lithium titanate is, for example, Li 4 Ti 5 O 12 Lithium metal phosphate is, for example, LiFePO 4 , LiMnPO 4 , LiCoPO 4 , and LiNiPO 4 Transition metal oxides include, for example, V 2 O 5 , and MoO 3 Lithium storage intermetallic compounds include, for example, Mg 2 Sn, Mg 2 Ge, Mg 2 Sb and Cu 3 Sb etc. Examples of lithium alloys include Li-Au, Li-Mg, Li-Sn, Li-Si, Li-Al, Li-B, Li-C, Li-Ca, Li-Ga, Li-Ge, Li-As, Li-Se, Li-Ru, Li-Rh, Li-Pd, Li-Ag, Li-Cd, Li-In, Li-Sb, Li-Ir, Li-Pt, Li-Hg, Li-Pb, Li-Bi, Li-Zn, Li-Tl, Li-Te, and Li-At. Examples of Si alloys include alloys with metals such as Li, and may also be alloys with at least one metal selected from the group consisting of Sn, Ge, and Al. The shape of the positive electrode active material is not particularly limited, and may be particulate. When the positive electrode active material is particulate, the positive electrode active material may be primary particles or secondary particles. A coating layer containing a Li-ion conductive oxide may be formed on the surface of the positive electrode active material, because this can suppress the reaction between the positive electrode active material and the solid electrolyte. Examples of Li-ion conductive oxides include LiNbO 3 , Li 4 Ti 5 O 12 , and Li 3 PO 4 The thickness of the coating layer is, for example, 0.1 nm or more, and may be 1 nm or more. On the other hand, the thickness of the coating layer is, for example, 100 nm or less, and may be 20 nm or less. The coating layer may cover, for example, 70% or more of the surface of the positive electrode active material, or may cover 90% or more.
[0027] As the solid electrolyte, the same ones as those exemplified in the solid electrolyte layer can be exemplified. The content of the solid electrolyte in the positive electrode layer is not particularly limited, but may be, for example, within a range of 1 mass % to 80 mass % when the total mass of the positive electrode layer is taken as 100 mass %.
[0028] The conductive material may be a known material, such as a carbon material and metal particles. The carbon material may be at least one selected from the group consisting of acetylene black, furnace black, VGCF, carbon nanotubes, and carbon nanofibers. In particular, from the viewpoint of electronic conductivity, at least one selected from the group consisting of VGCF, carbon nanotubes, and carbon nanofibers may be used. The metal particles may be particles of Ni, Cu, Fe, SUS, etc. The content of the conductive material in the positive electrode layer is not particularly limited.
[0029] Examples of the binder include acrylonitrile butadiene rubber (ABR), butadiene rubber (BR), polyvinylidene fluoride (PVdF), styrene butadiene rubber (SBR), etc. The content of the binder in the positive electrode layer is not particularly limited.
[0030] The thickness of the positive electrode layer is not particularly limited, but may be, for example, 10 to 100 μm, or 10 to 20 μm.
[0031] The positive electrode layer can be formed by a conventionally known method. For example, a positive electrode active material and, if necessary, other components are put into a solvent and stirred to prepare a slurry for the positive electrode layer, and the slurry for the positive electrode layer is applied onto one side of a support and dried to obtain a positive electrode layer. Examples of the solvent include butyl acetate, butyl butyrate, mesitylene, tetralin, heptane, and N-methyl-2-pyrrolidone (NMP). The method for applying the positive electrode layer slurry onto one surface of the support is not particularly limited, and examples thereof include a doctor blade method, a metal mask printing method, an electrostatic application method, a dip coating method, a spray coating method, a roll coating method, a gravure coating method, and a screen printing method. The support can be appropriately selected from those having self-supporting properties and is not particularly limited. For example, metal foils such as Cu and Al can be used.
[0032] As another method for forming the positive electrode layer, the positive electrode layer may be formed by pressure molding a powder of a positive electrode mixture containing a positive electrode active material and other components as necessary. When the powder of the positive electrode mixture is pressure molded, a press pressure of about 1 MPa to 2000 MPa is usually applied. The method of applying pressure is not particularly limited, but examples thereof include a method of applying pressure using a plate press, a roll press, or the like.
[0033] [Positive electrode current collector] The positive electrode current collector may be a known metal that can be used as a current collector for an all-solid-state battery. Examples of such metals include metal materials containing one or more elements selected from the group consisting of Cu, Ni, Al, V, Au, Pt, Mg, Fe, Ti, Co, Cr, Zn, Ge, and In. Examples of the positive electrode current collector include SUS, aluminum, nickel, iron, titanium, and carbon. The shape of the positive electrode current collector is not particularly limited, and may be in various shapes such as a foil shape, a mesh shape, etc. The thickness of the positive electrode current collector varies depending on the shape, but may be, for example, in the range of 1 μm to 50 μm, or in the range of 5 μm to 20 μm.
[0034] [Negative electrode] The negative electrode includes a negative electrode layer and a negative electrode current collector.
[0035] [Negative electrode layer] The negative electrode layer contains at least a negative electrode active material, and optionally contains a solid electrolyte, a conductive material, a binder, and the like. The negative electrode active materials include graphite, mesocarbon microbeads (MCMB), highly oriented pyrolytic graphite (HOPG), hard carbon, soft carbon, lithium, lithium alloys, Si, Si alloys, and Li 4 Ti 5O 12 As the lithium alloy and the Si alloy, the same ones as those exemplified in the positive electrode active material can be used. The shape of the negative electrode active material is not particularly limited, and examples thereof include a particulate shape, a plate shape, etc. When the negative electrode active material is particulate, the negative electrode active material may be primary particles or secondary particles. The conductive material and binder used in the negative electrode layer may be the same as those exemplified in the positive electrode layer. The solid electrolyte used in the negative electrode layer may be the same as those exemplified in the solid electrolyte layer. The thickness of the negative electrode layer is not particularly limited, but may be, for example, 10 to 100 μm, or 10 to 20 μm. The content of the negative electrode active material in the negative electrode layer is not particularly limited, and may be, for example, 20% by mass to 90% by mass.
[0036] [Negative electrode current collector] The material of the negative electrode current collector may be a material that does not alloy with Li, such as SUS, copper, and nickel. The shape of the negative electrode current collector may be, for example, a foil or a plate. The planar shape of the negative electrode current collector is not particularly limited, and may be, for example, a circle, an ellipse, a rectangle, or any polygonal shape. The thickness of the negative electrode current collector varies depending on the shape, and may be, for example, in the range of 1 μm to 50 μm, or in the range of 5 μm to 20 μm.
[0037] [Solid electrolyte layer] The solid electrolyte layer includes at least a solid electrolyte. As the solid electrolyte contained in the solid electrolyte layer, a known solid electrolyte that can be used in an all-solid-state battery can be appropriately used, and examples of such solid electrolytes include inorganic solid electrolytes such as sulfide-based solid electrolytes, oxide-based solid electrolytes, hydride-based solid electrolytes, halide-based solid electrolytes, and nitride-based solid electrolytes. The sulfide-based solid electrolyte may contain sulfur (S) as a main component of the anion element. The oxide-based solid electrolyte may contain oxygen (O) as a main component of the anion element. The hydride-based solid electrolyte may contain hydrogen (H) as a main component of the anion element. The halide-based solid electrolyte may contain halogen (X) as a main component of the anion element. The nitride-based solid electrolyte may contain nitrogen (N) as a main component of the anion element.
[0038] The sulfide-based solid electrolyte may be a sulfide glass, a crystallized sulfide glass (glass ceramics), or a crystalline material obtained by subjecting a raw material composition to a solid-phase reaction treatment. The crystalline state of the sulfide-based solid electrolyte can be confirmed, for example, by subjecting the sulfide-based solid electrolyte to powder X-ray diffraction measurement using CuKα radiation.
[0039] Sulfide glass is a raw material composition (e.g., Li 2 S and P 2 S 5 The amorphous material can be obtained by subjecting the mixture of the above to an amorphous treatment, such as mechanical milling.
[0040] Glass ceramics can be obtained, for example, by heat treating a sulfide glass. The heat treatment temperature may be any temperature higher than the crystallization temperature (Tc) of the sulfide glass observed by thermal analysis, and is usually 195° C. or higher. On the other hand, there is no particular upper limit to the heat treatment temperature. The crystallization temperature (Tc) of the sulfide glass can be measured by differential thermal analysis (DTA). The heat treatment time is not particularly limited as long as the desired crystallinity of the glass ceramic is obtained, but is, for example, within the range of 1 minute to 24 hours, and particularly within the range of 1 minute to 10 hours. The method of heat treatment is not particularly limited, but may be, for example, a method using a baking furnace.
[0041] Examples of oxide-based solid electrolytes include solid electrolytes containing Li, Y (Y is at least one of Nb, B, Al, Si, P, Ti, Zr, Mo, W, and S), and O. Specific examples of oxide-based solid electrolytes include Li 7 La 3 Zr 2 O 12 , Li 7-x La 3 (Zr 2-x Nb x )O 12 (0≦x≦2), Li 5 La 3 Nb 2 O 12 Garnet-type solid electrolytes such as (Li,La)TiO 3 , (Li,La)NbO 3 , (Li,Sr)(Ta,Zr)O 3 Perovskite-type solid electrolytes such as Li(Al,Ti)(PO 4 ) 3 , Li(Al,Ga)(PO 4 ) 3 Nasicon type solid electrolyte; Li 3 PO 4 , LIPON (Li 3 PO 4 Li-PO solid electrolytes such as Li 3 BO 3 , Li 3 BO 3 Examples of such solid electrolytes include Li-BO based compounds in which some of the O in the above formula is replaced with C.
[0042] The hydride-based solid electrolyte has, for example, Li and a complex anion containing hydrogen. The complex anion is, for example, (BH 4) - , (NH 2 ) - , (AlH 4 ) - , and (AlH 6 ) 3- etc. can be mentioned. As the halide-based solid electrolyte, for example, Li 6-3z Y z X 6 (X is at least one of Cl and Br, and z satisfies 0 < z < 2) etc. can be mentioned. As the nitride-based solid electrolyte, for example, Li 3 N etc. can be mentioned.
[0043] The shape of the solid electrolyte may be particulate from the viewpoint of good handleability. The average particle diameter of the particles of the solid electrolyte is not particularly limited, but for example, it is 10 nm or more, and may be 100 nm or more. On the other hand, the average particle diameter of the particles of the solid electrolyte is, for example, 25 μm or less, and may be 10 μm or less.
[0044] In the present disclosure, unless otherwise specified, the average particle diameter of the particles is the value of the volume-based median diameter (D50) measured by laser diffraction / scattering particle size distribution measurement. Further, in the present disclosure, the median diameter (D50) is the diameter (volume average diameter) at which the cumulative volume of the particles becomes half (50%) of the total volume when the particles are arranged in order from the particles with a small particle diameter.
[0045] The solid electrolyte can be used alone or in combination of two or more. Further, when using two or more solid electrolytes, two or more solid electrolytes may be mixed, or layers of two or more solid electrolytes may be formed respectively to form a multilayer structure. The proportion of the solid electrolyte in the solid electrolyte layer is not particularly limited, but for example, it is 50% by mass or more, and may be in the range of 60% by mass or more and 100% by mass or less, may be in the range of 70% by mass or more and 100% by mass or less, or may be 100% by mass.
[0046] The solid electrolyte layer may contain a binder from the viewpoint of expressing plasticity, etc. Examples of such binders include the materials exemplified as the binders used in the positive electrode layer. However, in order to facilitate high output, the binder may be contained in the solid electrolyte layer in an amount of 5 mass% or less from the viewpoint of preventing excessive aggregation of the solid electrolyte and enabling the formation of a solid electrolyte layer having a uniformly dispersed solid electrolyte.
[0047] The thickness of the solid electrolyte layer is not particularly limited, and is usually 0.1 μm or more and 1 mm or less. The method of forming the solid electrolyte layer includes a method of applying a slurry for the solid electrolyte layer containing a solid electrolyte onto a support and drying it, and a method of pressurizing a powder of a solid electrolyte material containing a solid electrolyte. The support can be the same as those exemplified for the positive electrode layer. When pressurizing the powder of the solid electrolyte material, a press pressure of about 1 MPa to 2000 MPa is usually applied. The method of applying pressure is not particularly limited, but may be any of the pressure applying methods exemplified in the formation of the positive electrode layer.
[0048] The all-solid-state battery may, as necessary, include an exterior body that houses an electrode laminate including a positive electrode current collector, a positive electrode layer, a solid electrolyte layer, a negative electrode layer, and a negative electrode current collector in this order, and a restraining member and the like. The material of the exterior body is not particularly limited as long as it is stable to the electrolyte, and examples of the material include polypropylene, polyethylene, and resins such as acrylic resin. The restraining member may be any known member usable as a restraining member for an all-solid-state battery, as long as it can apply a restraining pressure in the stacking direction to the electrode laminate. For example, a restraining member having a plate-shaped portion that sandwiches both surfaces of the electrode laminate, a rod-shaped portion that connects the two plate-shaped portions, and an adjustment portion that is connected to the rod-shaped portion and adjusts the restraining pressure by a screw structure or the like can be used. The adjustment portion can apply a desired restraining pressure to the laminate. The restraining pressure is not particularly limited, but may be, for example, 0.1 MPa or more, 1 MPa or more, or 5 MPa or more. By increasing the restraining pressure, there is an advantage that it is easier to improve the contact between the layers. On the other hand, the restraining pressure may be, for example, 100 MPa or less, 50 MPa or less, or 20 MPa or less. If the restraining pressure is too high, the restraining member is required to have high rigidity, and the restraining member may become large.
[0049] The all-solid-state battery may have only one of the above electrode laminates, or may be formed by laminating a plurality of the electrode laminates. The all-solid-state battery may be a primary battery or a secondary battery, but may be a secondary battery. The secondary battery can be repeatedly charged and discharged. The secondary battery is useful, for example, as an in-vehicle battery. The all-solid-state battery may be an all-solid-state lithium secondary battery or an all-solid-state lithium ion secondary battery. Examples of the shape of the all-solid-state battery include a coin type, a laminate type, a cylindrical type, and a square type. The use of the all-solid-state battery is not particularly limited, but examples thereof include power sources for vehicles such as hybrid electric vehicles (HEVs), plug-in hybrid electric vehicles (PHEVs), electric vehicles (BEVs), gasoline-powered vehicles, and diesel-powered vehicles. In particular, the all-solid-state battery may be used as a driving power source for hybrid electric vehicles, plug-in hybrid electric vehicles, or electric vehicles. The all-solid-state battery of the present disclosure may also be used as a power source for moving objects other than vehicles (e.g., railways, ships, and aircraft), and may also be used as a power source for electrical products such as information processing devices. EXAMPLES
[0050] Example 1 [Preparation of positive electrode layer] Using a rolling fluidized coating device (Powrex Corporation), the positive electrode active material particles (Li 1.15 Ni 1 / 3 Co 1 / 3 Mn 1 / 3 O 2The cathode active material particles having a lithium niobate coating layer were obtained by coating the cathode active material particles having a lithium niobate coating layer on the cathode active material particles having a lithium niobate coating layer and sintering the coated cathode active material particles in an air atmosphere. In a polypropylene container, PVdF, the above positive electrode active material particles, and a sulfide-based solid electrolyte (Li 2 SP 2 S 5 A SiO2-based glass ceramic) and VGCF (manufactured by Showa Denko K.K.) were added, and the resulting slurry for the positive electrode layer was stirred for 30 seconds with an ultrasonic dispersing device (UH-50 manufactured by SMT Corporation). Next, the container was shaken for 3 minutes with a shaker (TTM-1 manufactured by Shibata Scientific Co., Ltd.), and the slurry for the positive electrode layer was further stirred for 30 seconds with an ultrasonic dispersion device. After shaking the container for 3 minutes with a shaker, the slurry for the positive electrode layer was applied to the aluminum foil by the blade method using an applicator. Then, the slurry for the positive electrode layer was naturally dried and dried for 30 minutes on a hot plate at 100 ° C. to obtain a positive electrode mixture on the aluminum foil (substrate). The laminate of the aluminum foil (substrate) and the positive electrode mixture was densified at 4t / cm to obtain a positive electrode layer on the aluminum foil (substrate). The amount of the slurry for the positive electrode layer applied was adjusted so that the thickness of the positive electrode layer obtained when the positive electrode mixture was densified at 4t / cm was 15 μm.
[0051] [Preparation of negative electrode] In a polypropylene container, PVdF and negative electrode active material particles (Li 4 Ti 5 O 12 (LTO) particles) and the same sulfide-based solid electrolyte (Li 2 SP 2 S 5 A sintered body (aluminum-based glass ceramic) was added, and the resulting slurry for the negative electrode layer was stirred for 30 minutes with an ultrasonic dispersing device. The slurry for the negative electrode layer was applied to copper foil by the blade method using an applicator. The slurry for the negative electrode layer was then naturally dried, and then dried on a hot plate at 100°C for 30 minutes to obtain a negative electrode having a negative electrode layer on the copper foil (negative electrode current collector). The slurry for the negative electrode layer was then similarly applied to the back side of the copper foil (negative electrode current collector) and dried, forming a negative electrode layer on the back side of the copper foil (negative electrode current collector).
[0052] [Preparation of solid electrolyte layer] A polypropylene container was filled with heptane, BR, and a sulfide-based solid electrolyte (Li 2 SP 2 S 5 A crystalline cellulose-based glass ceramic was added, and the obtained solid electrolyte layer slurry was stirred for 30 seconds with an ultrasonic dispersion device. Next, the container was shaken for 30 minutes with a shaker (TTM-1 manufactured by Shibata Scientific Co., Ltd.), and the solid electrolyte layer slurry was further stirred for 30 seconds with an ultrasonic dispersion device. After shaking the container for 3 minutes with a shaker, the solid electrolyte layer slurry was applied onto an aluminum foil by a blade method using an applicator. The solid electrolyte layer slurry was then naturally dried and dried on a hot plate at 100°C for 30 minutes to form a solid electrolyte layer on the aluminum foil as a substrate.
[0053] [Preparation of carbon-coated aluminum foil (positive electrode current collector)] The furnace black conductive material and the PVdF binder were weighed to be 25:75 vol%. Then, NMP was added to prepare a carbon coat composition. Next, the carbon coat composition was applied to one side of the aluminum foil to a film thickness of 2 μm, and the carbon coat composition was dried at 100 ° C. for 1 hour to obtain a carbon-coated aluminum foil. The carbon-coated aluminum foil was cut to an aluminum foil size of 69.0 mm × 73.0 mm (carbon coat size of 69.0 mm × 71.0 mm). Then, a hot melt adhesive (Haibon ZH234-1, Hitachi Chemical) was applied to one side of the carbon-coated aluminum foil in a dot pattern starting from a point W = 2.25 mm in the width direction and H = 3 mm in the depth direction from the edge of the surface, so that the adhesive pitch (the distance x between adjacent adhesive parts) was 3 mm, forming an adhesive layer on the surface. A hot melt adhesive (Hybon ZH234-1, Hitachi Chemical) was applied to the back surface of the carbon-coated aluminum foil in a dot pattern starting from a point 3.75 mm wide and 3 mm deep from the edge of the surface, so that the adhesive pitch (distance x between adjacent adhesive parts) was 3 mm, forming an adhesive layer on the back surface. The deviation y of the adhesive parts on the front and back surfaces was 1.5 mm.
[0054] [Laminated body production] The solid electrolyte layers were laminated on both sides of the negative electrode so that each negative electrode layer and each solid electrolyte layer were in direct contact with each other, and pressed at 1.6 t / cm. Then, the aluminum foil substrate was peeled off from each solid electrolyte layer. Next, the positive electrode layer was laminated on each solid electrolyte layer so that the positive electrode layer and the solid electrolyte layer were in direct contact with each other, and pressed at 1.6 t / cm. Then, the aluminum foil substrate was peeled off from each positive electrode layer, and the obtained laminate was pressed at 5 t / cm and 170° C. Then, the positive electrode layer was laser trimmed to a size of 70.0 mm×70.0 mm, and the negative electrode was cut to a size of 72.0 mm×72.0 mm. Then, for each positive electrode layer, the electrode layer height was measured perpendicular to the three coating boundaries, the distance between adjacent peaks and valleys was measured, and the minimum of these was calculated as the curvature width, which was 6 mm.
[0055] [Attachment of carbon-coated aluminum foil] Then, a terminal was welded to the laminate. A carbon-coated aluminum foil (positive electrode current collector) was attached to the positive electrode layer on one side of the laminate via an adhesive layer to obtain a laminate-carbon-coated aluminum foil joint. Ten such joints were produced, and the carbon-coated aluminum foil of the joint and the laminate were attached via an adhesive layer to obtain ten joints. Carbon-coated foil was attached to one side of the positive electrode layer on the side of the joints on both ends where the carbon-coated aluminum foil was not attached, to obtain a stack of all-solid-state batteries.
[0056] Example 2 In [Preparation of carbon-coated aluminum foil (positive electrode current collector)], the adhesive was applied in a dot pattern on one side of the carbon-coated aluminum foil starting from a position at a width direction W = 1.5 mm and a depth direction H = 2 mm from the edge of the surface direction of the front surface so that the pitch x between the adhesive parts was 2 mm, forming an adhesive layer on the front surface, and the adhesive was applied in a dot pattern on the back surface of the carbon-coated aluminum foil starting from a position at a width direction W = 2.5 mm and a depth direction H = 2 mm from the edge of the surface direction of the back surface so that the pitch x between the adhesive parts was 2 mm, forming an adhesive layer on the back surface. An all-solid-state battery was obtained in the same manner as in Example 1. The deviation y of the adhesive parts on the front and back surfaces was 1 mm.
[0057] Example 3 In the [Preparation of the laminate (electrode laminate)], the laminate was pressed at room temperature instead of at 170° C. After that, the curvature width of each positive electrode layer was measured and found to be 10 mm. In addition, in [Preparation of carbon-coated aluminum foil (positive electrode current collector)], the adhesive was applied in a dot pattern on one side of the carbon-coated aluminum foil starting from a position at a width direction W = 3 mm and a depth direction H = 4 mm from the end of the surface direction of the front surface so that the pitch x between the adhesive parts was 4 mm, forming an adhesive layer on the front surface, and the adhesive was applied in a dot pattern on the back surface of the carbon-coated aluminum foil starting from a position at a width direction W = 5 mm and a depth direction H = 4 mm from the end of the surface direction of the back surface so that the pitch x between the adhesive parts was 4 mm, forming an adhesive layer on the back surface. Except for these, an all-solid-state battery was obtained in the same manner as in Example 1. The deviation y of the adhesive parts on the front and back surfaces was 2 mm.
[0058] Example 4 In [Preparation of carbon-coated aluminum foil (positive electrode current collector)], the adhesive was applied in a dot pattern on one side of the carbon-coated aluminum foil starting from a position at a width direction W = 1.5 mm and a depth direction H = 1.5 mm from the end of the surface direction of the front surface so that the pitch x between the adhesive parts was 2.8 mm, forming an adhesive layer on the front surface, and the adhesive was applied in a dot pattern on the back surface of the carbon-coated aluminum foil starting from a position at a width direction W = 2.5 mm and a depth direction H = 2.5 mm from the end of the surface direction of the back surface so that the pitch x between the adhesive parts was 2.8 mm, forming an adhesive layer on the back surface. In addition, a positive electrode layer with a curved width of 8.4 mm was used for each positive electrode layer. A solid-state battery was obtained in the same manner as in Example 1 except for these. The deviation y of the adhesive parts on the front and back surfaces was 1.4 mm.
[0059] Comparative Example 1 In [Preparation of carbon-coated aluminum foil (positive electrode current collector)], the adhesive was applied in a dot pattern on one side of the carbon-coated aluminum foil starting from a position W=3 mm in the width direction and H=4 mm in the depth direction from the edge of the front surface so that the pitch x between adhesive portions was 4 mm, forming an adhesive layer on the front surface, and the adhesive was applied in a dot pattern on the back surface of the carbon-coated aluminum foil starting from a position W=5 mm in the width direction and H=4 mm in the depth direction from the edge of the back surface so that the pitch x between adhesive portions was 4 mm, forming an adhesive layer on the back surface. An all-solid-state battery was obtained in the same manner as in Example 1. The deviation y of the adhesive portions on the front and back surfaces was 2 mm.
[0060] Comparative Example 2 An all-solid-state battery was obtained in the same manner as in Example 1, except that in [Preparation of carbon-coated aluminum foil (positive electrode current collector)], an adhesive was applied to the back surface of the carbon-coated aluminum foil in a dot pattern starting from a point 1.75 mm in the width direction and 3 mm in the depth direction H from the end of the surface direction of the back surface, so that the pitch x between the adhesive parts was 3 mm, to form an adhesive layer on the back surface. The deviation y of the adhesive parts on the front and back surfaces was 0 mm.
[0061] Comparative Example 3 An all-solid-state battery was obtained in the same manner as in Example 1, except that in [Preparation of carbon-coated aluminum foil (positive electrode current collector)], an adhesive was applied to the back surface of the carbon-coated aluminum foil in a dot pattern starting from a point 1.75 mm in the width direction W and 3 mm in the depth direction H from the end of the surface direction of the back surface, so that the adhesive pitch x was 3 mm, to form an adhesive layer on the back surface. The deviation y of the adhesive portions on the front and back surfaces was 0.5 mm.
[0062] Comparative Example 4 In [Preparation of carbon-coated aluminum foil (positive electrode current collector)], the adhesive was applied in a dot pattern on one side of the carbon-coated aluminum foil starting from a position at a width direction W = 3 mm and a depth direction H = 2.25 mm from the end of the surface direction of the front surface so that the adhesive pitch x was 3 mm, forming an adhesive layer on the front surface, and the adhesive was applied in a dot pattern on the back surface of the carbon-coated aluminum foil starting from a position at a width direction W = 3 mm and a depth direction H = 2.75 mm from the end of the surface direction of the back surface so that the adhesive pitch x was 3 mm, forming an adhesive layer on the back surface. An all-solid-state battery was obtained in the same manner as in Example 1. The deviation y of the adhesive part on the front surface and the back surface was 0.5 mm. The measurement of the curvature width of each positive electrode layer in Comparative Example 4 was performed for the curvature parallel to the coating boundary.
[0063] [Resistance evaluation method] Each solid-state battery was subjected to constant current constant voltage (CCCV) charging (cut current 0.01C) at an upper limit voltage of 2.95V and a rate of 1C, and then CCCV discharging (cut current 0.01C) at a lower limit voltage of 1.50V and a rate of 1C. The voltage of each solid-state battery was set to 2.36 V, and it was charged at a constant current (CC) rate of 2 C for 10 s, and the resistance of each solid-state battery was calculated from the change in voltage. It was then heated at 80°C and the resistance was measured again. The results are shown in Table 1.
[0064] [Table 1]
[0065] [Evaluation Results] As shown in Table 1, it is clear that the post-heating resistance of the all-solid-state batteries of Examples 1 to 4 is lower than the post-heating resistance of the all-solid-state batteries of Comparative Examples 1 to 4. [Explanation of symbols]
[0066] 1 Adhesive section 2 Current collector 3 electrode layer x Pitch y deviation (shortest distance) z deviation amount
Claims
[Claim 1] A component for an all-solid-state battery having a first electrode layer, a current collector, and a second electrode layer in this order, a part of a contact surface of each of the first electrode layer and the second electrode layer with the current collector is bonded to the current collector by an adhesive layer; the adhesive layer is composed of a plurality of adhesive portions arranged in a stripe pattern or a dot pattern on a contact surface between the current collector and each of the electrode layers, where x is the distance between adjacent adhesive portions on the same surface, and y is the shortest distance in a surface direction between the adhesive portion on the front surface side and the adhesive portion on the back surface side of the current collector when viewed in a plane, 2y / x≧1 is satisfied, A structure, characterized in that a curvature width R of each of the electrode layers measured at an interface with the current collector satisfies R≧2x.
Citation Information
Patent Citations
Energy device and its manufacturing method
JP2006185662A
All-solid battery
JP2017204377A
laminate
JP2020129518A
All-solid battery, method for manufacturing battery element, and method for manufacturing all-solid battery
JP2021150126A
Solid-state battery
WO2019181097A1